Antibiofilm and anti-caries effects of an experimental mouth rinse containing Matricaria chamomilla L. extract under microcosm biofilm on enamel - Braga, Aline Silva; Simas, Leticia Lobo de Melo; Pires, Juliana Gonçalves; Souza, Beatriz Martines; de Melo, Fernanda Pereira de Souza Rosa [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Dokkedal, Anne Ligia [UNESP]; Magalhães, Ana Carolina (Elsevier, 2020)
Objective: This study evaluated the antibiofilm and anti-caries effects of an experimental mouth rinse containing aqueous extract of Matricaria chamomilla L. Methods: Microcosm biofilm was produced on bovine enamel, from pooled human saliva mixed with McBain saliva, under 0.2 % sucrose exposure, for 5 days. The biofilm was daily treated using (1 mL/1 min): Vochysia tucanorum Mart. (2.5 mg/mL); Myrcia bella Cambess. (1.25 mg/mL); Matricaria chamomilla L. (20 mg/mL); Malva sylvestris (Malvatricin® Plus–Daudt); 0.12 % Chlorhexidine (PerioGard®-Palmolive, Positive control) and PBS (Negative control). The % dead bacteria, biofilm thickness, EPS biovolume, lactic acid concentration, the CFU counting (total microorganisms, Lactobacillus sp., total streptococci and Streptococcus mutans/S. sobrinus) were determined. Enamel demineralization was measured by TMR. Results: All mouth rinses induced bacterial death compared to PBS (p < 0.0001). The biofilm thickness varied from 12 ± 2 μm (chlorhexidine) to 18 ± 2 μm (V. tucanorum) (ANOVA/Tukey, p < 0.0001). The EPS biovolume varied from 7(4)% (chlorhexidine) to 30(20)% (PBS) (Kruskal-Wallis/Dunn, p < 0.0001). The lactic acid production was reduced by M. sylvestris (1.1 ± 0.2 g/L) and chlorhexidine (0.6 ± 0.2 g/L) compared to PBS (2.6 ± 1.3 g/L) (ANOVA, p < 0.0001). Malva sylvestris and chlorhexidine showed significant low CFU for total microorganisms, Lactobacillus sp. and total streptococci. Only chlorhexidine significantly reduced S. mutans/S. sobrinus. CFUs for total streptococci and Lactobacillus sp, were also significantly reduced by M. chamomilla L. Malva sylvestris (63.4 % of mineral loss reduction), chlorhexidine (47.4 %) and M. chamomilla L. (39.4 %) significantly reduced enamel demineralization compared to PBS (ANOVA/Tukey, p < 0.0001). Conclusion: M. chamomilla L. has lower antibiofilm action, but comparable anti-caries effect to those found for chlorhexidine, under this model. Clinical relevance: This study shows that the antibiofilm and anti-caries potential may vary between the commercial and experimental mouth rinses containing natural agents, with promising results for those containing Matricaria chamomilla L. and Malva Sylvestris.
Keywords: Dental caries; Enamel; Microcosm biofilm; Mouth wash; Natural agents